KEMAMPUAN PEMAHAMAN MATEMATIS SISWA MTs PADA MATERI BANGUN DATAR SEGIEMPAT DENGAN MENGGUNAKAN PENDEKATAN KONTEKSTUAL - Kurniasari, Ita; Sariningsih, Ratna (IKIP Siliwangi, 2018)
This research has purpose to analyze the ability of Mathematical Understanding of MTs students by using contextual approach. This research is a classroom action research with student population of MTs Nurul Hikmah located in West Bandung district and the sample is 18 students of class VIII. The instruments used in this research are cycle I and II tests (after giving the action); and the use of observation sheets for teachers and students as a measure of the conditions of action implementation. The procedures of this study consist of: (1) Planning, (2) Implementation of action, (3) Observation (4) evaluation, and (5) Reflection. The results showed that the Mathematical Understanding of MTs students on the rectangular building materials could be improved by using a contextual approach